(untitled) (Journal of Universal Science Research, 2025)
This article talks about the ancient history, cultural and aesthetic significance of the Uzbek national doppelgängers. Doppi-not only a headdress, but also a symbol of the culture, tradition, philosophy of life and striving for beauty of the people. Each region’s distinctive style of doppi represent distinct meaning and symbolic concepts through their patterns, decorations, and colors.